Development Of Micro Heating Element By Optical Lithography On Alumina Substrate - Tan, Teong Sheng (Universiti Sains Malaysia, 2017)
Optical lithography has been used to deposit resist coatings with desired pattern on flat substrate typically silicon wafer. Yet, rather little attention has been given to the development of Fe-Cr-Al alloys on alumina substrate. Thus, a particular interest has been given to the study of Fe-Cr-Al alloys deposition on alumina substrate as micro heating element of low temperature range thermionic energy converter. The features of micro heating element were printed on alumina substrate to form a SU-8 resist mask by optical lithography method. Micro heating element of Fe-Cr-Al alloy obtained by stripping the SU-8 resist after thermal evaporation, have been studied and measured by SEM. The resist on alumina substrate were not stripped completely even using NMP solvent as the lift-off solvent. The surface irregularities and porosity of as-sintered alumina has caused the resist to diffuse into the pores and adhere strongly to the alumina surface. The resist remains on the surface of alumina substrate even after ultrasonic agitation was used to energies the stripping process. The feature dimension of micro heating element on alumina substrate deviate from the desired dimension due to surface irregularities which leads to pattern deviation.